How does authentic leadership support employee resilience? An explanation from cognitive-affective personality system theory - Li, Xu; Li, Bingrong (Frontiers in Psychology, 2026)
The sustainable development of organizations depends on how employees develop resilience in the face of unexpected crises and changes. Leadership has been proven to have an important impact on employee resilience. Therefore, the paper explores how authentic leadership supports employee resilience through the cognitive-affective perspective. In study 1, the authors conducted a scenario experiment and recruited 247 MBA students to participate. In study 2, the authors collected two-wave data from 424 employees and 85 leaders in China. Findings reveal that authentic leadership effectively enhances employee resilience by strengthening employee vigor and role breadth self-efficacy (RBSE). Besides, employee traditionality is found to negatively moderate the relationship between authentic leadership and employee vigor, whereas its moderating effect on the link between authentic leadership and RBSE is non-significant. This research enriches the literature on employee resilience and provides valuable insights for improving the effectiveness of organizational leadership.